Factors Influencing the Diploma in Accounting (DIA) Students' Decision to Pursue Professional Accounting Programmes - Noorain, Omar (2009)
This study examines the influence of (1) Gender; (2) Cumulative Grade Point Average(CGPA); (3) Level of English; (4) Parent’s educational background; (5) Availability of study grant; (6) Personal attributes and (7) Students’ perception on the Diploma in Accounting (DIA) students’ decision to pursue professional accounting programmes. Based on a survey of 66 graduating students of part 6, 7 & 8, the findings reveal that CGPA and the availability of study grant are the two main variables found to be significant in influencing the DIA students’ decision to pursue professional accounting programmes. The results would be useful to the Faculty of Accountancy of UiTM to formulate the appropriate strategy to improve the CGPA achievement and to have a clear cut policy on financial supports.